Water-relation Parameters of Individual Mesophyll Cells of the Crassulacean Acid Metabolism Plant Kalanchoë daigremontiana - Steudle, Ernst (1980)
Water-relation parameters of leaf mesophyll cells of the CAM plant Kalanchoë daigremontiana have been determined directly in cells of tissue slices using the pressure-probe technique. Turgor pressures measured in cells of the second to fourth layer from the cut surface showed an average of 1.82 ± 0.62 bar (mean ± sd; n = 157 cells). This was lower than expected from measurements of the osmotic pressure of the cell sap. The half-time (T(1/2)) for water-flux equilibration of individual cells was 2.5 to 8.8 seconds. This is the fastest T(1/2) found so far for higher-plant cells. The calculated values of the hydraulic conductivity were in the range of 0.20 to 1.6 × 10(−5) centimeters second(−1) bar(−1), with an average of (0.69 ± 0.46) × 10(−5) centimeters second(−1) bar(−1) (mean ± sd; n = 8 cells). The T(1/2) values of water exchange of individual cells are consistent with the overall rates of water-flux equilibration measured for tissue slices. The volumetric elastic moduli (∈) of individual cells were in the range 13 to 128 bar for turgor pressures between 0.0 and 3.4 bar; the average ∈ value was 42.4 ± 27.7 bar (mean ± sd; n = 21 cells). This ∈ value is similar to that observed for other higher-plant cells. The water-storage capacity of individual cells, calculated as C(c) = V/(∈ + π(i)) (where V = cell volume and π(i) = internal osmotic pressure) was 9.1 × 10(−9) cubic centimeters bar(−1) per cell, and the capacity for the tissue was 2.2 × 10(−2) cubic centimeters bar(−1) gram(−1) fresh weight. The significance of the water-relation parameters determined at the cellular level is discussed in terms of the water relations of whole leaves and the high water-use efficiency characteristic of CAM plants.